Assessment Of Medical Doctor’s Knowledge, Perception, And Willing-ness Toward Telemedicine In Three Siloam Hospitals In Bali Island - Rilly Richard Mamahit; Mochammad Mukti Ali (Green Publisher Indonesia, 2024)
This study assesses the knowledge, perception, and willingness of medical doctors toward telemedicine at three prominent hospitals in Bali: Siloam Hospitals Denpasar, Bali International Medical Centre Kuta, and Bali International Medical Center Nusa Dua. The research involved a cross-sectional quantitative approach using a questionnaire distributed to 40 participating general practitioners and specialists. Key findings revealed that while most doctors are familiar with telemedicine, there remains a variance in their perception and willingness to adopt it, largely influenced by demographic factors such as age, gender, and practice type. Despite the ongoing growth of telemedicine, the study highlights the need for targeted training and awareness programs to ensure its effective integration into healthcare services.